Study of human T and B lymphocytes with heterologous antisera: IV. Subpopulations in tonsil and adenoid cell suspensions - Brochier, J. (1978)
Mononuclear cells from eighty-seven human tonsils and fourteen adenoids were examined for T and B cells and their subpopulations. Forty six percent of the tonsil cells were killed in the presence of C by an antiserum specific for T cells and 41.7% were able to form E rosettes. Among them 58% were `active' E rosettes and 24% possessed Fc μ receptors as compared to 35 and 37%, respectively, in peripheral blood. Fifty percent of cells were detected by an antiserum recognizing B cells and monocytes; most of them bore surface immunoglobulins and complement receptors. None of the cells bound chicken erythrocytes coated with rabbit IgG. Only 1 to 3% of monocytes were detected by the peroxidase staining. Significant variations depending on the age of the donors were noticed: T cells increased from 42% in infants to 54.6% in adults whereas the B cells dropped from 56.2 to 38.5%. Similar distributions of cells were found in adenoids and tonsils of donors of the same age. About 2 to 3% of tonsil cells contained cytoplasmic immunoglobulins, more than one third of them being of the IgG class. The proliferative response of adenoid or tonsil cells to Con A, PWM and NWSM was similar to that of blood lymphocytes although their relative numbers of T and B cells were very different, whereas their response to PHA and ALG was slightly lower.